2018
DOI: 10.1177/1099636218792671
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance of marine sandwich composites subjected to flatwise compression and flexural loading: Effect of resin pins

Abstract: Mechanical performance of marine sandwich panels comprising E-glass/vinyl ester face sheets and perforated poly-vinyl chloride foam core was evaluated and compared with conventional foam core sandwich panels. Circular holes through the foam core thickness were drilled with 12 different arrangements in square patterns and the holes were filled with the resin during the infusion process which created the through-the-thickness solid resin pins. The effect of each pattern on the flatwise compression and core shear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 29 publications
0
20
0
1
Order By: Relevance
“…12). For the PF sample, the core carried the compression force alone and when the compression force reached its peak, the curve showed a large plateau region (Balıkoğlu, Demircioğlu, Yıldız, Arslan, & Ataş, 2020). However, the compression loads of the GSF samples are primarily carried by the resin grids.…”
Section: Flatwise Compression Test Resultsmentioning
confidence: 99%
“…12). For the PF sample, the core carried the compression force alone and when the compression force reached its peak, the curve showed a large plateau region (Balıkoğlu, Demircioğlu, Yıldız, Arslan, & Ataş, 2020). However, the compression loads of the GSF samples are primarily carried by the resin grids.…”
Section: Flatwise Compression Test Resultsmentioning
confidence: 99%
“…The pins stiffened and strengthened the PVC foam against low shear loads, while the foam core supported the pins and prevented the premature shear failure. 30 The FEA successfully captured the initial stiffness and the post yield response of the PRFS specimens. PRFS_Ø2, 4R specimens failed due to compressive upper face sheet failure under the loading points while PRFS_Ø2, 4S specimens failed by core shear failure.…”
Section: Load-displacement Curvesmentioning
confidence: 99%
“…1417 Therefore, the influence of core modifications on the mechanical properties of sandwich structures has been investigated by a number of researchers. 18–33 Mitra 18 revealed the efficiency of introducing the semi-circular shaped grooves into the sandwich panels to improve the shear performance. It was shown that the delamination initiation load of sandwich composite columns subjected to in-plane compressive loading could be increased approximately 25% by inserting pre-manufactured shear keys in foam-core grooves.…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of innovation in the design of sandwich cores include shearkeying [15], tube-reinforced foam [16], composite rods [17], polymer/resin pins [18][19][20] and hybrid divided cores [21].…”
Section: Introductionmentioning
confidence: 99%